The extent to which language teachers use linguistic artificial intelligence applications: an analysis based on selected variables - Fayyoumi, Khalil Abdel Rahman; Yassin, Baderaddin; Almarashdi, Hanan; Al-Khawaldeh, Mohammed; Al-Fayyoumi, Somayyah Khalil (Frontiers in Education, 2025)
The purpose of the study was to investigate the degree to which language teachers in Jordan t use linguistic artificial intelligence (AI) applications in the teaching process, considering some demographic and professional characteristics. A descriptive analytic methodology was used. The population of the study included all language teachers at the Education Directorate of the Amman District (N = 304). The study sample comprised (128) language teachers from primary and secondary schools. A questionnaire was developed and distributed electronically; 54 of them were retrieved, yielding a response rate of 42.1%. The study tool consisted of (43 items) divided into eight domains: smart electronic educational games applications, augmented reality, smart chatbots, virtual reality, smart evaluation and tests, the Internet of Things, adaptive learning environment applications, and smartphone applications. The study results indicated that the level of use of linguistic artificial intelligence technology applications among language teachers was high, and that there were statistically significant differences in the use of technology applications by language teachers. Linguistic artificial intelligence is attributed to gender differences in favor of females, and the educational stage in favor of primary and secondary school teachers, while there are no statistically significant differences in the use of linguistic artificial intelligence technology applications by language teachers due to differences in academic qualifications or years of experience.